2006
DOI: 10.1007/bf03175000
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activities of marine epibiotic bacteria isolated from brown algae of Japan

Abstract: One hundred and sixteen epibiotic bacteria were isolated from the surface of nine species of brown algae Sargassum serratifolium, S. fusiforme, S. filicinum, Padina arborescens, Undaria pinnatifida, Petalonia fascia, Colpomenia sinuosa, Scytosiphon lomentaria and Ecklonia cava which were collected at Awaji Island, Japan. Primary screening results using disc-diffusion assay revealed that, among the bacteria isolated 20% of epibiotic bacteria exhibited antibacterial activity. Among them, 10 bacteria which showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(31 citation statements)
references
References 33 publications
0
24
0
3
Order By: Relevance
“…Burgess et al (2003) isolated several bacteria with high antifouling activity and found that most of these bacteria belonged to Bacillus, such as B. pumilus, B. licheniformis and B. subtilus. Kanagasabhapathy et al (2006) have isolated B. pumilus and other Bacillus species from different brown alga. Kanagasabhapathy et al (2008) investigated antimicrobial activity of epiphytic bacteria from several red algae and found that the highest activity was produced by certain Bacillus species especially B. cereus and B. pumilus.…”
Section: Discussionmentioning
confidence: 99%
“…Burgess et al (2003) isolated several bacteria with high antifouling activity and found that most of these bacteria belonged to Bacillus, such as B. pumilus, B. licheniformis and B. subtilus. Kanagasabhapathy et al (2006) have isolated B. pumilus and other Bacillus species from different brown alga. Kanagasabhapathy et al (2008) investigated antimicrobial activity of epiphytic bacteria from several red algae and found that the highest activity was produced by certain Bacillus species especially B. cereus and B. pumilus.…”
Section: Discussionmentioning
confidence: 99%
“…Marine living surfaces are often inhabited by diverse and complex communities of bacteria (2,13,14,17,18,35,36) and hence harbor biodiversity, ecological processes, and biotechnological potential distinct from those of surrounding planktonic communities (7, 19-21, 24, 39, 41). Bacterial epiphytic communities on algae have been studied in terms of nutrient acquisition (5,10), carbon exchange (4), resistance to biofouling (6,37), the production of bioactive compounds (1,14), and, perhaps most notably, the lack of the host's normal morphological development in the absence of a bacterial community (23,25,30,32).…”
mentioning
confidence: 99%
“…Bacterial epiphytic communities on algae have been studied in terms of nutrient acquisition (5,10), carbon exchange (4), resistance to biofouling (6,37), the production of bioactive compounds (1,14), and, perhaps most notably, the lack of the host's normal morphological development in the absence of a bacterial community (23,25,30,32).…”
mentioning
confidence: 99%
“…Surfaces of marine organisms have been documented to host a higher percentage of antimicrobial compound producing bacteria when compared to surrounding marine environments (Zheng et al 2005). Up to 20 % of bacteria isolated from brown seaweeds have been reported to exhibit antibacterial activity (Kanagasabhapathy et al 2006). Three isolates (MA_6, NA_1 and NSA_10) were active against the Gram-negative indicator P. putida (ATCC27853) ( Table 3).…”
Section: Screening Of S Rugosum Isolates For Antimicrobial Activitymentioning
confidence: 99%